2011
DOI: 10.4328/jcam.78
|View full text |Cite
|
Sign up to set email alerts
|

Use of Chest Computed Tomography in Stable Patients with Blunt Thoracic Trauma: Clinical and Forensic Perspective

Abstract: Özet AmaçBu çalışmanın amacı künt travmalı stabil hastalarda bilgisayarlı toraks tomografisinin klinik ve adli önemini araştırmaktı. Gereç ve YöntemlerTravma sonrası 24 saat içinde akciğer grafisi ve bilgisayarlı toraks tomografisi çekilen künt toraks travmalı 50 hasta retrospektif olarak incelendi. Hastaların dağılımı, torasik lezyonlar, tedavi yöntemleri ve adli sorunları incelendi. Bulgular Çalışmamızda, en sık tespit edilen lezyon kot fraktürü idi. Bilgisayarlı göğüs tomografisi torasik lezyonların tespiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It is reported that occult pneumomediastinum resolved in average 3 hours after the initial exam [2]. CT exams are more sensitive to detect free mediastinal air than chest X-ray and the expanding use of CT scan for first assessment plays a role not only in diagnosing mediastinal air but also in the management of trauma patients, in particular, those with blunt chest trauma [3,6]. Another feature expected from CT is the ability to detect possible esophageal injuries with high sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that occult pneumomediastinum resolved in average 3 hours after the initial exam [2]. CT exams are more sensitive to detect free mediastinal air than chest X-ray and the expanding use of CT scan for first assessment plays a role not only in diagnosing mediastinal air but also in the management of trauma patients, in particular, those with blunt chest trauma [3,6]. Another feature expected from CT is the ability to detect possible esophageal injuries with high sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Radiologic evaluation is important for the diagnosis and management at this prospect. In this regard, multidetector computed tomography (MDCT) plays a key role in the setting of thoracic blunt trauma [3]. However, its controversial utility and benefits in trauma patients, oral contrast administration in proper patients can aid in diagnosis by narrowing the differentials in terms of esophageal perforation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the accurate, rapid and reliable diagnosis of pneumothorax, and its occult type is the primary issue for trauma management and writing accurate medicolegal reports, because an extremely small pneumothorax may progress, especially when mechanical ventilation and general anesthesia are used, and may reach life-threatening sizes. 3,14,19,20 Therefore, thoracic CT should be employed for the appropriate diagnosis and treatment of OPTX, to more accurately determine this potentially life threatening condition especially among those who have experienced traumatic chest injuries.…”
Section: Discussionmentioning
confidence: 99%